KONSTRUKSI SOSIAL BUDAYA DAN RELASI GENDER TERHADAP MITOS KESEHATAN REPRODUKSI PEREMPUAN SUKU DAYAK DI PALANGKARAYA - Siminto, Siminto; Irawati, Retno Purnama (LP2M IAIN Palangka Raya, 2013)
This study is to explore the peopleâ perceptions about the Dayaknese women reproduction health myth and gender relation that is related to women Dayaknese health in Palangkaraya. This study used descriptive qualitative type. To take sample of this study was done by random sampling. The population target of this study were choosen by using special selection that of the subject of this study were the inhabitant who lives in Palangka Raya without using gender discriminated.Â The mythes which are related to dayaknese women reproduction health showed that there were some related construction to social and cultural which were full gender imbalances. If they are related to the myth, so the distinction system between woman and man are constructed to some mythes. The above mythes declared that the real constructions were from the way of men to think, so it showed that the wowen had restrictiveness to make action in their daily life.Â The above mythes declared that the pregnant woman should not sew the cloth, go fishing, sit with the legs crossed, should use rings in her anklet, should abstain to eat some food. It showed that the systems of men thoughts were to delimitate of women actions. The main positive of this study showed the most respondents have got the different perception to this myth of this time. The responses of respondents considered that the mythes were not significant anymore at the present time. The perceptions of respondents came out like this because there are some changes to the way of thinking and their educational level are more and more getting better. Besides that, the old generations had not informed anymore about mythes to their children, with the result that there are some young generation did not know about mythes. Â Â